The Influence of Abduh’s Principle On Rashid Rida - ahmad nabil amir (Minhaj: Jurnal Ilmu Syariah, 2020)
This paper analyze the influence of Muhammad ‘Abduh on his chief disciple, Muhammad Rashid Rida. Rida was the leading advocate of Abduh’s rational principle and modern ideas through his writing in Tafsir al-Manar (The Manar Commentary) and Tarikh al-Ustadh al-Imam Muhammad Abduh (Biography of Muhammad Abduh). Tafsir al-Manar is a Qur’anic exegesis based on rational approach outlined by Muhammad ‘Abduh and the Tarikh is a comprehensive biography of the life and works of Muhammad Abduh printed in three volumes that significantly documented Abduh’s lasting influence and legacy in modern Egypt. Rida continued to resolutely champion the ideas of reform through Majallat al-Manar (al-Manar Journal) that highly reverberated Abduh’s principles and remarkably claimed extensive influence in contemporary Islamic world.